Special Position of Ashabah’s Heirs in the Sunni Islamic Jurisprudence of Inheritance: A Sociohistorical Approach - Akhmad Jalaludin; Md Yazid Ahmad (Asy-Syari'ah, 2024)
This study discusses the relationship between the position of male relatives in relation to the heir, either directly or through a male lineage, and not through females (known as ‘aṣabah) in Sunni jurisprudence, within the context of the Arab anthropological background. Sunni jurisprudence assigns a special position to ‘aṣabah. Regardless of how distant the familial relationship of an ‘aṣabah is to the heir, they are not excluded except by another ‘aṣabah. This study employs a normative juridical approach with a sociohistorical and ushul fiqh perspective to explore the connection between the ‘aṣabah system in Islamic inheritance law and the sociohistorical backdrop of Arab society during the development of Islamic jurisprudence by Sunni scholars, especially focusing on the kinship system. The findings indicate that the ‘aṣabah system in the Sunni fiqh is an interpretation of the Qur'anic texts and Hadith, and that this interpretation is heavily influenced by the Arab kinship system, which is deeply rooted in a patrilineal local cultural context. The author argues that the association of the ‘aṣabah system with the local cultural practices of Arab society conflicts with several inheritance principles in the Qur'an, such as the principle that men and women with the same degree of kinship should have equal inheritance rights, the principle of bilateral inheritance, and the principle of prioritizing closer relatives.